2018
DOI: 10.1186/s12891-018-2227-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of the intervertebral disc and ossification of posterior longitudinal ligament in children

Abstract: BackgroundIDC in children, first reported by Baron in 1924, is very rare. OPLL of the cervical spine mainly affect people ages 50–70 years. The coexistence of IDC and OPLL in children is very rare, only six cases with 3 to 24 months’ follow-up were reported to date.Case presentationA 6-year-old boy presented with complains of neck pain at July 2007. The boy was treated by conservative treatment and observed up for 9 years. Neck pain greatly improved after a one-month conservative treatment and never recur. Lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The exact cause of IDC accompanied by OPLL is still unclear. However, trauma is often considered an inducer because some children’s disc calcifications occur before trauma[ 12 , 13 ]. Beluffi et al [ 9 ] suggested that there are two types of IDC: Symptomatic and asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The exact cause of IDC accompanied by OPLL is still unclear. However, trauma is often considered an inducer because some children’s disc calcifications occur before trauma[ 12 , 13 ]. Beluffi et al [ 9 ] suggested that there are two types of IDC: Symptomatic and asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Simple IDC disappears in 3 to 60 mo, with an average of 15 mo[ 8 ]. However, after 9 years of follow-up, Du et al [ 4 , 12 ] found that residual IDC persisted and the height of the affected intervertebral space had become narrow, indicating that residual IDC may not subside spontaneously with time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Surgical treatment is effective that can create possibilities for the recovery of nerve function. 9,10 For the patients with three or more segments OPLL in Kline positive, posterior approach surgery is recommend. 11 Since the range of most OPLL is below C2 level in clinical, the general scope of surgery is C3-7 laminectomy or expansive laminoplasty.…”
mentioning
confidence: 99%